Forest fragmentation in the landscape in the Atlantic Forest Biome: A systematic review of the literature - Cunha, Stephany Diolino; Crivilin, Bruna Sampaio; Araújo, Matheus da Silva; Borges, Luís Antônio Coimbra (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
Forest fragmentation is defined as the process by which a continuous area of habitat is reduced in size and divided between spaces. Therefore, due to the increase in these areas, this study aimed to conduct a systematic review of the literature on forest fragments in the Atlantic Forest biome in order to verify their main characteristics and landscape ecology. Publications in search platforms referring to the period from 2000 to 2020 were analyzed such as: SciELO, Google academic and CAPES journals portal. The search terms entered were: “Studies of forest fragments in the Atlantic Forest biome” and “Landscape ecology in forest fragments”. A total of 15 articles were selected from among the works found, and 5 of these were chosen to be evaluated in the present study. Four of the five works were carried out in the state of Espírito Santo, close to basins and sub-basins, and only one work was carried out in a state park. Thus, the evaluated works with the theme, study of fragmentation and ecology of the landscape showed a high degree of fragmentation, meaning that they have fragments smaller than 5 hectares; in addition, all fragments have an irregular edge effect. Therefore, measures aimed at the conservation of biodiversity are needed in all places so that there is ecological restoration of the landscape and conservation of fauna and flora in the Atlantic Forest biome.